Total marrow irradiation in hematopoietic stem cell transplantation for hematologic malignancies - Kerbauy, Mariana Nassif; Arcuri, Leonardo Javier; Favareto, Sergio Leonardo; de Rezende, Ana Carolina Pires; Hamerschlak, Nelson (Frontiers in Medicine, 2023)
Total body irradiation (TBI) has been an essential component of the conditioning regimen in hematopoietic cell transplantation for many years, however, higher doses of TBI reduce disease relapse at the expense of greater toxicities. Total marrow irradiation and total marrow and lymphoid irradiation have been developed to deliver organ-sparing targeted radiotherapy.Data from different studies show that TMI and TMLI can be safely administered in escalating doses in association with different chemotherapy conditioning regimen protocols, in situations with unmet needs, such as multiple myeloma, high-risk hematologic malignancies, relapsed or refractory leukemias, and elderly or frail patients, with low rates of transplant-related mortality. We reviewed the literature on the application of TMI and TMLI techniques in autologous and allogeneic hematopoietic stem cell transplantation in different clinical situations.